Protective effect of bixin on carbon tetrachloride-induced hepatotoxicity in rats - Moreira, Priscila R. [UNESP]; Maioli, Marcos A. [UNESP]; Medeiros, Hyllana C. D. [UNESP]; Guelfi, Marieli [UNESP]; Pereira, Flavia T. V. [UNESP]; Mingatto, Fabio E. [UNESP] (Soc Biolgia Chile, 2014)
Background: The liver is an important organ for its ability to transform xenobiotics, making the liver tissue a prime target for toxic substances. The carotenoid bixin present in annatto is an antioxidant that can protect cells and tissues against the deleterious effects of free radicals. In this study, we evaluated the protective effect of bixin on liver damage induced by carbon tetrachloride (CCl4) in rats.Results: The animals were divided into four groups with six rats in each group. CCl4 (0.125 mL kg(-1) body wt.) was injected intraperitoneally, and bixin (5.0 mg kg(-1) body wt.) was given by gavage 7 days before the CCl4 injection. Bixin prevented the liver damage caused by CCl4, as noted by the significant decrease in serum aminotransferases release. Bixin protected the liver against the oxidizing effects of CCl4 by preventing a decrease in glutathione reductase activity and the levels of reduced glutathione and NADPH. The peroxidation of membrane lipids and histopathological damage of the liver was significantly prevented by bixin treatment.Conclusion: Therefore, we can conclude that the protective effect of bixin against hepatotoxicity induced by CCl4 is related to the antioxidant activity of the compound.
Keywords: Bixin; Carbon tetrachloride; Hepatotoxicity; Oxidative stress; Protective activity